Vom erstrebenswertesten Leben : Aristoteles' philosophie der Musse - Varga, Simon (Topics in ancient philosophy ;, 2014)
Aristotle examines the role of leisure (scholé) in the optimal life of the citizen (Politics VII/VIII). In the quest for the most desirable life- understood as the proper combination of political and contemplative elements- Aristotle ascribes an important role to leisure. Varga explores the two books in terms of the notion of scholé and shows the inadequacy of previous interpretations of Aristotle's proposed design for the commonwealth.